2020
DOI: 10.1186/s13018-020-01871-8
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient vs. inpatient hip arthroplasty: a matched case-control study on a 90-day complication rate and 2-year patient-reported outcomes

Abstract: Background: The transition to outpatient-based surgery is a major development occurring in recent years in the field of total hip arthroplasty (THA). The effect of this transition on patient-reported outcomes (PROs) is still not well established. The purpose of the current study was to compare patients undergoing inpatient THA (iTHA) to patients undergoing outpatient THA (oTHA) regarding (1) perioperative variables including surgical time, blood loss, and length of stay (2) 90-day complication rates and unplan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
(45 reference statements)
1
22
0
Order By: Relevance
“… 3 , 10 - 27 A study comparing the complication rates and patient-reported outcome measures (PROMs) between inpatient and day-case THA showed that at 90 days postoperatively there were no significant differences in complication rates between the two groups, and the latter group experienced better PROMs at two years. 13 Similarly, Coenders et al 26 demonstrated significant improvement in all PROMs at one year following day-case THA, but also significantly lower 90-day complication and readmission rates in day-case THA compared with inpatient THA (4.61% vs 11.54% and 1.38% vs 4.46%, respectively). Moreover, Richards et al 15 conducted a matched cohort analysis that showed lower 90-day complication rates in patients who underwent day-case THA compared to those that were treated as an inpatient post-operatively (8.82% vs 10.29%, respectively).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“… 3 , 10 - 27 A study comparing the complication rates and patient-reported outcome measures (PROMs) between inpatient and day-case THA showed that at 90 days postoperatively there were no significant differences in complication rates between the two groups, and the latter group experienced better PROMs at two years. 13 Similarly, Coenders et al 26 demonstrated significant improvement in all PROMs at one year following day-case THA, but also significantly lower 90-day complication and readmission rates in day-case THA compared with inpatient THA (4.61% vs 11.54% and 1.38% vs 4.46%, respectively). Moreover, Richards et al 15 conducted a matched cohort analysis that showed lower 90-day complication rates in patients who underwent day-case THA compared to those that were treated as an inpatient post-operatively (8.82% vs 10.29%, respectively).…”
Section: Introductionmentioning
confidence: 92%
“…The decision to use a general anaesthetic (GA) 13 , 15 , 16 , 21 , 25 , 27 or a regional anaesthetic (RA) (spinal or epidural) 3 , 10 - 12 , 14 - 16 , 18 - 27 for day-case THA is debateable. Rosinsky et al 13 is the only study using exclusively a GA as the form of anaesthetic. Berger et al 12 showed in their study involving 150 consecutive day-case THAs successfully discharged home on the same day, that a regional anaesthetic combined with adequate pre-emptive oral analgesia and anti-emetic therapy is an effective method of maximizing day-case discharge.…”
Section: Perioperative Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 In appropriately selected patients, outpatient TJA has been shown to be safe and effective, resulting in decreased hospital stays and reduced economic burden to the healthcare system without increasing complications, readmissions, or emergency department (ED) visits. 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 Furthermore, a recent large database study found that contemporary outpatient TJA is associated with fewer adverse events when matched to inpatient procedures. 20 Compared with inpatient TJA, patients who undergo outpatient TJA may also have higher satisfaction and improved patient-reported outcomes.…”
mentioning
confidence: 99%